2017
DOI: 10.3892/ijo.2017.3978
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness affects epithelial-mesenchymal transition of cervical cancer cells through miR-106b and its target protein DAB2

Abstract: The effects of different substrate stiffness were investigated on epithelial-mesenchymal transition (EMT) of cervical cancer cell lines and the role of miR-106b and its target protein DAB2 therein. Cervical cancer cell lines HeLa and SiHa were cultured on artificial substrates with different stiffness prepared using different ratios of acrylamide and bis-acrylamide. Changes of microRNA profiles were detected using microRNA chip analysis, and the expression levels of EMT-related markers E-cadherin and vimentin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…Cheng et al 15 found that DAB2 is identified as a direct target of miR-106b and it is inhibited by TGF-β1 partly through miR-106b and is involved in TGF-β1-induced CC cell migration. Piao et al 16 reported that miR-106 overexpression and DAB2 knockdown induced epithelial to mesenchymal transition (EMT) of CC cells cultured on substrate. As miR-106b plays an essential role in CC, its molecular mechanisms need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al 15 found that DAB2 is identified as a direct target of miR-106b and it is inhibited by TGF-β1 partly through miR-106b and is involved in TGF-β1-induced CC cell migration. Piao et al 16 reported that miR-106 overexpression and DAB2 knockdown induced epithelial to mesenchymal transition (EMT) of CC cells cultured on substrate. As miR-106b plays an essential role in CC, its molecular mechanisms need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that miR‐106b regulates the EMT of cancer cells and promotes tumor progression . It is also noted that, upon EMT inducement, cancer cells exhibit morphological changes and a couple of EMT‐related molecules including E‐cadherin, vimentin, ck19, Snail, and N‐cadherin.…”
Section: Resultsmentioning
confidence: 99%
“…First, molecular phenotypes of CTCs were associated with various behavior of cancer cells including anoikis resistance metastasis and therapeutic resistance. It has been reported that miR‐106b promotes anoikis resistance and EMT processes in breast cancer cells by targeting RB and Snail gene . Acquisition of a more malignant phenotype for CTC might easily explain the resistance to elimination strategies such as chemotherapy, local antigrowth signaling, and immune attack by the host.…”
Section: Discussionmentioning
confidence: 99%
“…Some other literatures have also demonstrated that DAB2 is regulated by various miRNAs at the post‐transcriptional level in multiple cancer types. For instance, miR‐106b is involved in TGFβ1‐induced cell migration by targeting DAB2 in cervical carcinoma . MiR‐93 promotes cell growth and invasion in nasopharyngeal carcinoma by targeting DAB2 .…”
Section: Discussionmentioning
confidence: 99%